1977
DOI: 10.1037/0096-1523.3.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Serial reaction time as a function of the nature of repeated events.

Abstract: Past research into the phenomenon of reduced latency to repeated events in serial reaction time tasks resulted in attempts to partition reaction time into components attributable to separate cognitive processes. These attempts focused on many-to-one condensing paradigms, which permitted direct assessment of the effect of response-only repetitions but not stimulus-only repetitions. The three experiments reported in the present study used a technique designed to overcome this limitation. It was found that repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
(31 reference statements)
2
11
0
Order By: Relevance
“…If the effect is perceptual, on the other hand, the effect should persist. Ells and Gotts (1977) reported an experiment with some similarities to this. In their study, subjects performed a Sternberg memory-scanning task of a go-no-go variety, responding whenever the probe belonged to the memory set.…”
Section: Experiments 6: Repetition and Response Modalitymentioning
confidence: 67%
“…If the effect is perceptual, on the other hand, the effect should persist. Ells and Gotts (1977) reported an experiment with some similarities to this. In their study, subjects performed a Sternberg memory-scanning task of a go-no-go variety, responding whenever the probe belonged to the memory set.…”
Section: Experiments 6: Repetition and Response Modalitymentioning
confidence: 67%
“…A number of studies have found little direct benefit of response repetition, except when it has been accompanied by stimulus repetition (e.g., Ells & Gotts, 1977;Fletcher & Rabbitt, 1978;Krueger & Shapiro, 1981). Subjects may tend to repeat the same response if they recognize the current stimulus as similar to a previous one, bypassing the normal processes for response selection (Bertelson, 1963(Bertelson, , 1965.…”
Section: Discussionmentioning
confidence: 99%
“…However, other work failed to identify systematic facilitation associated with response repetition when the stimulus does not repeat (Ells & Gotts, 1977;Hinrichs & Krainz, 1970;Li & A. F. Smith, 1992; M. C. Smith, 1968;Williams, 1966). Fletcher (1981) concluded that the presence or absence of repetition effects depends on practice: Early in practice, subjects displaya strong stimulus repetition effect, which progresses into a response repetition effect later in practice (see also Bertelson, 1965;Rabbitt, 1968).…”
Section: Sequence Effectsmentioning
confidence: 99%